PENINGKATAN KETERAMPILAN BERPIKIR KRITIS MENGGUNAKAN METODE ETH PADA MATA PELAJARAN IPA MI - Purwantoro, Farich (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the influence of the Everyone is a Teacher Here (ETH) approach on the critical thinking skills of fifth-grade students at MI Raudlatul Hasan Condong. The research employs a quantitative method with six meetings, including four lecture sessions, one pre-test, and one post-test. The study sample consists of 25 students from class V B as the control group and 26 students from class V A as the experimental group. Data were collected through tests and non-test methods, while data analysis was conducted by comparing pre-test and post-test results and using N-Gain analysis to assess the development of critical thinking skills in both groups. The results indicate that students in the experimental class experienced an improvement in critical thinking skills, with an average N-Gain score of 0.71, which is higher than the control group’s average score of 0.25. Based on the data analysis, the ETH approach has been proven to have a positive impact on enhancing students' critical thinking skills